Pengaruh Keterlibatan Pemangku Kepentingan Terhadap Keberhasilan Proyek Konstruksi Rehabilitasi Jaringan Irigasi D.I. Buloila Kanan, Gorontalo - Patamani, Sarif; Afriadie, Chandra; Pratiwi, A. Andini Radisya (Jurnal sosial dan sains, 2025)
The success of a construction project is not only measured by the achievement of technical aspects such as cost, quality, and time, but is also greatly influenced by stakeholder engagement. This is increasingly relevant for irrigation network rehabilitation projects that have a strategic role in supporting food security. This study aims to analyze the influence of stakeholder involvement consisting of project owners (owner/promoters), planning consultants (designer/defender), regulators and regional authorities (latent), as well as the end-user community or the Water User Farmers Association (P3A/apathetic) on the success of the irrigation network rehabilitation project of D.I. Buloila Kanan, Gorontalo. The research method uses a quantitative approach by collecting primary data through questionnaires to respondents who are directly involved in the project, both from elements of the government, consultants, contractors, and the community. Data were analyzed using descriptive methods and inferential tests to determine the partial and simultaneous influence of stakeholder involvement on the success of the project. The results show that the involvement of each stakeholder has a significant effect on the success of the project. The project owner plays a role in the provision of budgets, operating policies, and maintenance (O&M). The planning consultant determines the technical quality of the design according to local hydrological and socio-economic conditions. Regulators and regional authorities facilitate the administrative process and synchronization of spatial planning. Meanwhile, P3A contributes to the sustainability of irrigation functions through active participation in operations and maintenance. Simultaneously, the involvement of all stakeholders strengthens the success of the project, both in terms of physical output and long-term benefits. The conclusion of this study confirms that synergy between stakeholders is the main determinant of the success of irrigation network rehabilitation projects.